2011
DOI: 10.1093/ndt/gfr024
|View full text |Cite
|
Sign up to set email alerts
|

Do two intravenous iron sucrose preparations have the same efficacy?

Abstract: Background. Intravenous (i.v.) iron sucrose similar (ISS) preparations are available but clinical comparisons with the originator iron sucrose (IS) are lacking.Methods. The impact of switching from IS to ISS on anaemia and iron parameters was assessed in a sequential observational study comparing two periods of 27 weeks each in 75 stable haemodialysis (HD) patients receiving i.v. iron weekly and an i.v. erythropoiesis-stimulating agent (ESA) once every 2 weeks. Patients received IS in the first period (P1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 14 publications
2
73
0
9
Order By: Relevance
“…The fi rst was of the substitution of a follow-on iron sucrose product (Ferex, BMI Korea) for the originator (Venofer®, Vifor Pharma Ltd, Switzerland) in gynaecological patients that resulted in signifi cantly more adverse events and higher overall costs [2]. The second was of inferior therapeutic effects and increase in costs seen after substitution of the follow-on Fer Mylan for Venofer® in French renal dialysis patients [3]. Substitutions were both based on theoretical cost savings and the clinicians were not aware of the switch until after they observed the negative effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fi rst was of the substitution of a follow-on iron sucrose product (Ferex, BMI Korea) for the originator (Venofer®, Vifor Pharma Ltd, Switzerland) in gynaecological patients that resulted in signifi cantly more adverse events and higher overall costs [2]. The second was of inferior therapeutic effects and increase in costs seen after substitution of the follow-on Fer Mylan for Venofer® in French renal dialysis patients [3]. Substitutions were both based on theoretical cost savings and the clinicians were not aware of the switch until after they observed the negative effects.…”
Section: Resultsmentioning
confidence: 99%
“…The adequacy of this regulatory approval process has been questioned because therapeutic non-equivalence and non-interchangeability of authorized follow-on IV iron sucrose products have been reported [2,3]. Therefore, authorities addressed the urgent need to defi ne best practices for nanosimilar approval and post-approval pharmacovigilance to maximize the chances that such follow-on products provide patients with non-inferior safety and clinical outcomes [4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…ISSs in Europe received marketing authorization through the generic drug pathway, suggesting interchangeability. Clinical reports such as reported in [10], however, have recently shown that IS and ISSs may not have the same or similar effi cacy and safety profi le, and thus appear not to be interchangeable. A regulatory pathway, comparable to the one applied for biosimilars, is therefore currently discussed as mentioned above.…”
Section: Special Reportmentioning
confidence: 98%
“…41 It was concluded that the follow-on product was not therapeutically equivalent to the reference iron-sucrose complex. 41 In addition, it was shown that the reference iron-sucrose preparation and its follow-on products had different effects on nitrosative stress, apoptosis, oxidative stress and biochemical and inflammatory markers in rats. 42 Therefore, on March 2011, the CHMP adopted a Reflection Paper on non-clinical studies for generic nanoparticle iron medicinal product applications.…”
Section: Follow-on Products Of Nbcdsmentioning
confidence: 99%